A Study of Short Term Outcomes among Covid-19 Patients Discharged without Follow up In the New York Metropolitan Area - Molmenti, Christine Louise; Mitra, Neil; Shah, Abhinit; Flynn, Anne; Brown, Zenobia; Baxter, Kathryn; Cekic, Vesna; Bleau, Hallie; Picone, Jacqueline; Olivieri, Christina; Allis, Debbie; Perlas, Patricia; et al. (Edelweiss Applied Science and Technology, 2021)
Background: A shortage of beds, high case volume, decreased availability of outpatient medical doctors, and limited disease knowledge resulted in the premature discharge and poor follow up of COVID-19 patients in the New York Metropolitan Area. Objective: The primary objective of this retrospective study and phone survey was to characterize the demographics and clinical outcomes (e.g., readmission rates, comorbidities, mortality, and functional status) of COVID-19 patients discharged without follow-up. The secondary objective was to assess the impact of race and comorbidities on readmission rates and the extent to which patients were escalated to another care provider. Methods: Electronic medical records were reviewed for COVID-19 patients discharged from 3 NYMA hospitals in March 2020. Follow up data regarding medical status, ability to perform activities of daily living and functional status was also obtained from patients via phone call. The Chi- square, Fishers exact test and t-tests were used to analyze the data. Results: 349 patients were included in the analysis. The hospital readmission rate was 10.6% (58.8% for pulmonary reasons) and did not differ by race. 74.3% of readmissions were <14 days after release. The post-discharge mortality rate was 2.6%. Hypertension was the most common comorbidity (43%). There was a statistically significant association between mortality and number of comorbidities (p=<0.0001). 82% of patients were contacted by phone. 66.6% of patients returned to pre-COVID baseline function in ≥1 month. As a result of information obtained on the follow up phone call, 4.2% of patients required “escalation” to another provider. Conclusion: Discharging COVID-19 patients without prearranged follow up was associated with high readmission and mortality rates. While the majority of patients recovered, prolonged weakness, lengthy recovery, and the need for additional medical intervention was noted. Further work to assess the effectiveness COVID-19 post-discharge programs is warranted.